?We're Still Here?: A Photovoice Study of Mothers' Perspectives 6 Years after the Flint Michigan Water Contamination Event (Mary Ann Liebert, 2021)
Purpose: This study explored the lived experiences of pregnant and parenting women after the water contamination event in Flint, Michigan (Flint Water Contamination Event [FWCE]), by helping them visualize their everyday challenges, assets, and family health concerns. Methods: The photovoice methodology was utilized in this study. Individual participants met with researchers to discuss their photos using the SHOWeD method. Researchers analyzed the photographs, accompanying narratives, and discussion session transcripts using descriptive coding and thematic analysis. Results: Data analysis revealed five themes: (1) having a healthy pregnancy and well children is a central concern in everyday life, (2) children serve as social and practical resources for family, (3) meeting children's need for safe water is a significant concern, (4) the community and its households battle to get safe affordable water, and (5) there are resources available in the community to support mothers. Conclusion: While much information is still being collected and published in the aftermath of the FWCE, this study was the first to use the photovoice method to allow pregnant and parenting women to express their concerns about how the FWCE continues to affect the health and care of their families.